2016
DOI: 10.1016/j.physbeh.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Variability of behavioral chronotypes of 16 mammalian species under controlled conditions

Abstract: This is an author-produced, peer-reviewed version of this article. © 2016, Elsevier. Licensed under the Creative Commons AttributionNonCommercial-No Derivatives 4.0 License. Details regarding the use of this work can be found at: http://creativecommons.org/licenses/by-nc-nd/ 4.0/ . The final, definitive version of this document can be found online at Physiology & Behavior, doi: 10.1016/j.physbeh.2016 Publication Information Refinetti, Roberto. (2016) E-mail address: refinetti@circadian.org (R. Refinetti). Abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
(45 reference statements)
3
22
0
Order By: Relevance
“…Studies of chronotypes of free-living and captive wild animals are at the intersection between chronobiology and ecology [97,98,141,165,166]. In some studies, measures of associated fitness consequences have provided hints to the rstb.royalsocietypublishing.org Phil.…”
Section: (B) Chronotypementioning
confidence: 99%
“…Studies of chronotypes of free-living and captive wild animals are at the intersection between chronobiology and ecology [97,98,141,165,166]. In some studies, measures of associated fitness consequences have provided hints to the rstb.royalsocietypublishing.org Phil.…”
Section: (B) Chronotypementioning
confidence: 99%
“…This means that all individual sheep initiated activity each day within a short, 40-min window, whereas individual cats initiated activity over the full course of the day. Importantly, the relatively intermediate human chronotype spread of 6 h was the same as that of the laboratory rat, being wider than those of 7 of the other species and narrower than those of 8 of the other species [55].…”
Section: Introductionmentioning
confidence: 82%
“…In human studies, which are predominantly based on surveys rather than actual activity records, it has been suggested that chronotype could be defined as the time of mid-sleep on free (non-working) days [13]. In animal studies [55] and human studies with actigraphic data [68], the time of activity onset on free days (every day for laboratory animals) has been of practical value and was chosen for this study.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations